2016
DOI: 10.1116/1.4971389
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Recommended reading list of early publications on atomic layer deposition—Outcome of the “Virtual Project on the History of ALD”

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 18 publications
0
37
0
1
Order By: Relevance
“…According to a recent review (Ahvenniemi, 2017), ALD was invented and developed independently with different names: molecular layering (ML) since the 1960s in the Soviet Union (Ahvenniemi, 2017;Shevjakov, 1967;Mokrushin, 2019), and atomic layer epitaxy (ALE) since the 1970s in Finland (Ahvenniemi, 2017;Suntola, 1977). In addition to ALD (Leskelä, 1990) it has also been called molecular deposition (Aleskovskii, 1979), atomic layer evaporation (ALE) (Ahonen, 1980), molecular stratification (Malygin, 1980), molecular lamination (Kopylov, 1981), chemical assembly (Egorov, 1984), molecular layer epitaxy (MLE) (Nishizawa, 1985) and atomic layer growth (ALG) (Aoyagi, 1987).…”
Section: Atomic Layer Deposition (Ald)mentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent review (Ahvenniemi, 2017), ALD was invented and developed independently with different names: molecular layering (ML) since the 1960s in the Soviet Union (Ahvenniemi, 2017;Shevjakov, 1967;Mokrushin, 2019), and atomic layer epitaxy (ALE) since the 1970s in Finland (Ahvenniemi, 2017;Suntola, 1977). In addition to ALD (Leskelä, 1990) it has also been called molecular deposition (Aleskovskii, 1979), atomic layer evaporation (ALE) (Ahonen, 1980), molecular stratification (Malygin, 1980), molecular lamination (Kopylov, 1981), chemical assembly (Egorov, 1984), molecular layer epitaxy (MLE) (Nishizawa, 1985) and atomic layer growth (ALG) (Aoyagi, 1987).…”
Section: Atomic Layer Deposition (Ald)mentioning
confidence: 99%
“…In addition to ALD (Leskelä, 1990) it has also been called molecular deposition (Aleskovskii, 1979), atomic layer evaporation (ALE) (Ahonen, 1980), molecular stratification (Malygin, 1980), molecular lamination (Kopylov, 1981), chemical assembly (Egorov, 1984), molecular layer epitaxy (MLE) (Nishizawa, 1985) and atomic layer growth (ALG) (Aoyagi, 1987). ALE is commonly known as the origin of ALD (Ahvenniemi, 2017).…”
Section: Atomic Layer Deposition (Ald)mentioning
confidence: 99%
“…The three-dimensional uniformity, also termed "conformality," is a consequence of the systematic use of repeated, selfterminating (saturating, irreversible), separated gas-solid reactions of at least two compatible compounds [1][2][3][4][5][6]. While the principles of ALD were formulated already in the 1960s and 1970s, independently twice [7][8][9][10][11][12][13][14], it was in the 1990s that ALD was promoted as a tool for nanotechnology [15] and during the 2000s that ALD has enabled the continuation of Moore's law of transistor miniaturisation [16]. By the end of 2010, over 700 two-reactant ALD processes had been developed [17].…”
Section: Introductionmentioning
confidence: 99%
“…To attain a certain thickness, a determined number of cycles is performed. A review of the origins of ALD and a recommended reading list can be found in Reference [2].…”
Section: Introductionmentioning
confidence: 99%